Civil liability arising from the damages of cyberbullying: Towards legal protection for victims in the digital environment - Sarah, Mohammad Ali Jehad (Journal of Economic, Administrative and Legal Sciences, 2025)
The researcher addressed the phenomenon of cyberbullying, which is considered one of the most prominent contemporary issues related to the negative use of technology and social media. This phenomenon is manifested in the use of the internet as a tool to harm others psychologically or morally, through insults, belittlement, defamation, or mockery. The researcher used the descriptive method in this study to define the phenomenon of cyberbullying, identify its types and various forms, and also employed the analytical method to study the legal texts contained in the Jordanian Civil Code, with the aim of analyzing the elements of civil liability arising from cyberbullying. The study showed that the harm resulting from cyberbullying affects the victim's emotions and dignity, as these actions cause tangible psychological and moral harm. The researcher recommended the necessity of enhancing the civil liability of the cyberbully, while also holding social media platforms jointly responsible if they fail to fulfill their legal duty of removing or limiting the spread of offensive content.
Keywords: bullying; cyberbullying; civil liability